2023
DOI: 10.24425/fmc.2022.144086
|View full text |Cite
|
Sign up to set email alerts
|

Adapting the OSCE to the times of the COVID-19 pandemic. A look at the e-OSCE from the students’ perspective

Abstract: a completely remote OSCE (e-OSCE) was conducted for the first time using the Microsoft Teams platform. 255 test takers were tasked with presenting their communication and clinical skills in order to assess clinical reasoning. A i m: Analysis of the assessment of the OSCE adaptation to the requirements of the COVID-19 pandemic at the Department of Medical Educations in the form of the e-OSCE from the students' perspective. M e t h o d s: Discussion of the OSCE modification was carried out among 6 th -year medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
0
0
1
Order By: Relevance
“…Das Prüfungsklima wurde insgesamt als angenehm empfunden. Im Gegensatz zu einer reinen Online-OSCE, wie in mehreren Studien untersucht [ 9 , 14 , 26 , 28 ], erfolgte diese virtuelle Prüfung als Präsenzveranstaltung mit hohem logistischem und personellem Aufwand. Da virtuelle Prüfungssituationen bis dato in der HNO-Heilkunde gänzlich unbekannt oder zumindest nicht eindeutig definiert waren, erschien eine hybride Konstellation vorteilhaft.…”
Section: Diskussionunclassified
“…Das Prüfungsklima wurde insgesamt als angenehm empfunden. Im Gegensatz zu einer reinen Online-OSCE, wie in mehreren Studien untersucht [ 9 , 14 , 26 , 28 ], erfolgte diese virtuelle Prüfung als Präsenzveranstaltung mit hohem logistischem und personellem Aufwand. Da virtuelle Prüfungssituationen bis dato in der HNO-Heilkunde gänzlich unbekannt oder zumindest nicht eindeutig definiert waren, erschien eine hybride Konstellation vorteilhaft.…”
Section: Diskussionunclassified
“…Many educational facilities for healthcare professionals, including residents, medical, nursing, pharmacy, and dentistry students, rapidly transitioned from traditional in-person OSCEs to virtual OSCEs (also described as remote OSCE, online OSCE, or tele-OSCE) (Felthun et al, 2021a;Malau-Aduli et al, 2022). These virtual OSCEs are satisfactory, feasible, and cost-effective as per survey results (Langenau et al, 2014;Shaban et al, 2021;Shaiba et al, 2021), questionnaire feedbacks (Skrzypek et al, 2022;Motkur et al, 2022;Garofalo et al, 2023), empirical analysis (Felthun et al, 2021b;Minty et al, 2022), and descriptive qualitative studies (Shorbagi et al, 2022;Saad et al, 2022;Thampy et al, 2022;). Although three studies assessed the reliability of virtual OSCEs by calculating Cronbach's alphas, and they were about 0.80 (Oliven et al, 2011(Oliven et al, , 2021Porto et al, 2023), a reliability analysis based on G-theory is yet to be reported (Kunutsor et al, 2022).…”
Section: Introductionmentioning
confidence: 99%